Non-site of memory located. Reflections on the dramas Rechnitz (The Exterminating Angel) by Elfriede Jelinek and Our Class by Tadeusz Słobodzianek - Żyła, Weronika (Free your mind: Reflections on language, literature and culture, 2022)
In this thesis, the author would like to consider whether a non-sites of memory can change its ontological status and become a site of memory, and whether such a process can occure in real space, or if a different medium is needed. The author will focus on two dramas, which tell about the analysed processes – Rechnitz (The Exterminatig Angel) by Elfriede Jelinek and Our Class by Tadeusz Słobodzianek – and their role in restoring the memory of the Holocaust. The stories of both places, which reveal the repeatedly duplicated mechanisms, also remain an important context, which makes it possible to believe that the process of restoring memory to non-sites of memory can be put in a universal framework.